Proteomics Analysis Revealed that Crosstalk between Helicobacter pylori and Streptococcus mitis May Enhance Bacterial Survival and Reduces Carcinogenesis - Khosravi, Yalda; Loke, Mun Fai; Goh, Khean Lee; Vadivelu, Jamuna (Frontiers in Microbiology, 2016)
Helicobacter pylori is the dominant species of the human gastric microbiota and is present in the stomach of more than half of the human population worldwide. Colonization by H. pylori causes persistent inflammatory response and H. pylori-induced gastritis is the strongest singular risk factor for the development of gastric adenocarcinoma. However, only a small proportion of infected individuals develop malignancy. Besides H. pylori, other microbial species have also been shown to be related to gastritis. We previously reported that interspecies microbial interaction between H. pylori and S. mitis resulted in alteration of their metabolite profiles. In this study, we followed up by analyzing the changing protein profiles of H. pylori and S. mitis by LC/Q-TOF mass spectrometry to understand the different response of the two bacterial species in a multi-species micro-environment. Differentially-expressed proteins in mono- and co-cultures could be mapped into 18 biological pathways. The number of proteins involve in RNA degradation, nucleotide excision repair, mismatch repair, and lipopolysaccharide (LPS) biosynthesis were increased in co-cultured H. pylori. On the other hand, fewer proteins involve in citrate cycle, glycolysis/ gluconeogenesis, aminoacyl-tRNA biosynthesis, translation, metabolism, and cell signaling were detected in co-cultured H. pylori. This is consistent with our previous observation that in the presence of S. mitis, H. pylori was transformed to coccoid. Interestingly, phosphoglycerate kinase (PGK), a major enzyme used in glycolysis, was found in abundance in co-cultured S. mitis and this may have enhanced the survival of S. mitis in the multi-species microenvironment. On the other hand, thioredoxin (TrxA) and other redox-regulating enzymes of H. pylori were less abundant in co-culture possibly suggesting reduced oxidative stress. Oxidative stress plays an important role in tissue damage and carcinogenesis. Using the in vitro co-culture model, this study emphasized the possibility that pathogen-microbiota interaction may have a protective effect against H. pylori-associated carcinogenesis.